Cho các số `a` và `b` dương thỏa mãn: `a^2010+b^2010=a^2011+b^2011=a^2012+b^2012` Tính giá trị bt: `A=a^2013+b^2013`

Cho các số `a` và `b` dương thỏa mãn:
`a^2010+b^2010=a^2011+b^2011=a^2012+b^2012`
Tính giá trị bt: `A=a^2013+b^2013`

1 bình luận về “Cho các số `a` và `b` dương thỏa mãn: `a^2010+b^2010=a^2011+b^2011=a^2012+b^2012` Tính giá trị bt: `A=a^2013+b^2013`”

  1. Ta có:
    (a^2012 + b^2012) – 2.(a^2011 + b^2011) + (a^2010 + b^2010) = 0
    <=> a^2010 (a^2 – 2a + 1) + b^2010 (b^2 – 2b + 1) = 0
    <=> a^2010 (a – 1)^2 + b^2010 (b -1)^2 = 0
    Vì (a – 1)^2 >= 0 , a^2010 > 0
    => a^2010 (a – 1)^2 >= 0
    Tương tự, b^2010 (b  – 1)^2 >= 0
    => a^2010 (a – 1)^2 + b^2010 (b -1)^2 >= 0
    mà a^2010 (a – 1)^2 + b^2010 (b -1)^2 = 0
    <=> {(a – 1 = 0),(b – 1 = 0):} <=> a = b = 1
    Vậy A = 1 + 1 = 2 tại a^2010 + b^2010 = a^2011 + b^2011 = a^2012 + b^2012 .

    Trả lời

Viết một bình luận

Câu hỏi mới